Regulation of the Stability and Localization of Post-synaptic Membrane Proteins by Liquid-Liquid Phase Separation - Hosokawa, Tomohisa; Liu, Pin-Wu (Frontiers in Physiology, 2021)
Synaptic plasticity is a cellular mechanism of learning and memory. The synaptic strength can be persistently upregulated or downregulated to update the information sent to the neuronal network and form a memory engram. For its molecular mechanism, the stability of α-amino-3-hydroxyl-5-methyl-4-isoxazolepropionate-type glutamate receptor (AMPAR), a glutamatergic ionotropic receptor, on the postsynaptic membrane has been studied for these two decades. Since AMPAR is not saturated on the postsynaptic membrane during a single event of neurotransmitter release, the number and nanoscale localization of AMPAR is critical for regulating the efficacy of synaptic transmission. The observation of AMPAR on the postsynaptic membrane by super-resolution microscopy revealed that AMPAR forms a nanodomain that is defined as a stable segregated cluster on the postsynaptic membrane to increase the efficacy of synaptic transmission. Postsynaptic density (PSD), an intracellular protein condensate underneath the postsynaptic membrane, regulates AMPAR dynamics via the intracellular domain of Stargazin, an auxiliary subunit of AMPAR. Recently, it was reported that PSD is organized by liquid-liquid phase separation (LLPS) to form liquid-like protein condensates. Furthermore, the calcium signal induced by the learning event triggers the persistent formation of sub-compartments of different protein groups inside protein condensates. This explains the formation of nanodomains via synaptic activation. The liquid-like properties of LLPS protein condensates are ideal for the molecular mechanism of synaptic plasticity. In this review, we summarize the recent progress in the properties and regulation of synaptic plasticity, postsynaptic receptors, PSD, and LLPS.